The Influence of E-WOM and Brand Attitude on the Purchase Intention of Skintific Skincare Products - Adisty, Syahva Salsabila Putri; Setyawan, Anton Agus; Wahyudi, Henri Dwi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: Information technology, which is currently undergoing continuous change, has brought great changes to human life. Where today, many people spend their time accessing the internet in carrying out daily activities and looking for information on goods and services. This study aims to analyze the effect of E-WOM, and Brand Attitude on Purchase Intention Methodology: This study uses quantitative methods, the sampling technique in this study is non-probability sampling with purposive sampling technique. The data collection method used in this study was the distribution of questionnaires with a Likret scale. The population in this study were consumers who were interested in purchasing skincare skintific. which amounted to 150 respondents. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS software which consists of Outer model and Inner model analysis Results: This study reveals that E-WOM and Brand Attitude variables can have a positive and significant effect on Purchase Intention Positive brand attitudes influence consumer priorities towards brands and purchases. This is because increasing brand valuation by consumers will also increase brand attitudes and can encourage consumer buying intentions. Brand attitude is considered a marker of consumer behavioral intentions Consumers. Applications/Originality/Value This study recommends skintific skincare management to strengthen and encourage customers to do testimonials about skintific products. With positive testimonials from consumers, it will encourage other consumers to have the intention to buy skintific products. In fact, testimonials provided by consumers who have purchased skintific products are able to encourage and convince the purchase of skintific products.